2009
DOI: 10.1063/1.3259383
|View full text |Cite
|
Sign up to set email alerts
|

Strain effect analysis on phonon thermal conductivity of two-dimensional nanocomposites

Abstract: In this paper, we present a model that combines lattice dynamics and the phonon Boltzmann transport equation (BTE) to analyze strain effect on the cross-plane phonon thermal conductivity of silicon wire-germanium host nanocomposites. For a given strain condition, mechanical strain is translated to crystal lattice deformation by using the Cauchy–Born rule. Strain-dependent phonon thermal properties of Si and Ge obtained from lattice dynamics with Tersoff empirical interatomic potential are then incorporated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…More importantly we notice that the general trend of κ(ε h ) variations obtained with Tersoff III potential, plotted in Fig. 2, is similar to the previously reported strain effects on the thermal conductivity of bulk silicon 7,11,15 and Si nanostructures 64,65 .…”
Section: Resultssupporting
confidence: 87%
“…More importantly we notice that the general trend of κ(ε h ) variations obtained with Tersoff III potential, plotted in Fig. 2, is similar to the previously reported strain effects on the thermal conductivity of bulk silicon 7,11,15 and Si nanostructures 64,65 .…”
Section: Resultssupporting
confidence: 87%
“…The experimental demonstration of utilizing strain to actively control phonon and thermal properties has been applied to many different kinds of material systems (Hsieh, et al, 2009;Hsieh, et al, 2011;Alam, et al, 2015). Theoretical studies have also been performed to understand the origins of strain-dependent thermal conductivity of both bulk crystals (Picu, et al, 2003;Bhowmick and Shenoy, 2006;Li, et al, 2010;Parrish, et al, 2014) and nanostructured materials (Xu and Li, 2009;Xu and Buehler, 2009;Li, et al, 2010). While it is necessary to quantify the strain dependence of thermal conductivity, it is still more challenging to precisely control the exerted strain in 2-D materials than in 3-D materials.…”
Section: Strain Effectsmentioning
confidence: 99%
“…The strain effects on the thermal conductivity in thin films and insulating solids have been explored by using molecular dynamic simulations [27][28][29]. The thermal conductivity of strained nanostructures such as two-dimensional nanocomposites, nanowires, and nanofilms also have been modeled and analyzed by the atomic method and continuum models [30][31][32]. The more relevant studies of straindependent thermal conductivity in GaN nanostructures revealed that the deformation along the axial directions of wires reduces the thermal conductivity linearly both in rectangular and triangu lar GaN nanowires [33,34], More recently, an experimental study has shown the strong strain-thermal conductivity coupling in the SiN thin film [35], For the sake of giving more complete insights into the strain/ stress-thermal conductivity coupling behavior in GaN nanostruc tures, it is cardinal that various deformation modes are needed to examined since the nanostructures could experience complex strain/stress circumstances in corresponding electronic devices.…”
Section: Introductionmentioning
confidence: 99%